Grammatical Cohesion of Writing Section in English Text Books “English for Nusantara” in Kurikulum Merdeka - Yenny Teriana; Safnil Arsyad (International Journal of Innovation and Education Research, 2025)
This study examined the grammatical cohesions in writing sections of the English textbooks English for Nusantara, which are intended for seventh and eighth-grade students in Indonesia under the Kurikulum Merdeka. For seventh and eighth grade levels, the study finds and contrasts cohesive devices like conjunctions, ellipses, references, and substitutions using Halliday and Hasan's cohesion framework. A structured observation checklist was used to analyze textbook material using a descriptive qualitative technique. The results show that the seventh-grade textbook uses a wider range of cohesive devices, with references accounting for the majority (66.2%), followed by conjunctions (27.2%). On the other hand, the eighth-grade textbook has no examples of replacement, ellipsis, or lexical coherence and instead mostly uses references (53%) and conjunctions (47%). The eighth-grade text's lack of ellipsis and a narrow variety of coherent devices point to a decrease in linguistic complexity. These findings point to possible discrepancies in grade-level advancement of cohesion tactics and emphasize the necessity of curriculum modifications to improve writing coherence in English language instruction. Keywords: Grammatical Cohesions, Textbooks, Writing